2021
DOI: 10.1021/acs.orglett.1c03310
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Trifunctionalized Cyclohexane Synthesis via a Diastereoselective Reductive Cope Rearrangement and Functional Group Interconversion Strategy

Abstract: Polyfunctionalized cyclohexanes are privileged scaffolds in drug discovery. Reported herein is a method for synthesizing 1,2,4-trifunctionalized cyclohexanes via diastereoselective reductive Cope rearrangement. The scaffolds obtained can be derivatized by orthogonal functional group interconversion to cyclohexanes bearing a 1-amide, 2-branched arylallyl, and variable 4-functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…To yield the targeted building blocks, we employed our previously reported "reductive Cope rearrangement" to drive forward the [3,3] process. 19,51,52 As such, promoting Cope rearrangement in the presence of Hantzsch ester resulted in full conversion and good yields and stereoselectivity for products 5a and 5b. Importantly, the enantioselective synthesis of products 4 is scalable; as shown in Scheme 2B, we efficiently prepared gram quantities of a representative building block 4b.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…To yield the targeted building blocks, we employed our previously reported "reductive Cope rearrangement" to drive forward the [3,3] process. 19,51,52 As such, promoting Cope rearrangement in the presence of Hantzsch ester resulted in full conversion and good yields and stereoselectivity for products 5a and 5b. Importantly, the enantioselective synthesis of products 4 is scalable; as shown in Scheme 2B, we efficiently prepared gram quantities of a representative building block 4b.…”
Section: Resultsmentioning
confidence: 91%
“…To yield the targeted building blocks, we employed our previously reported “reductive Cope rearrangement” to drive forward the [3,3] process. 19,51,52 As such, promoting Cope rearrangement in the presence of Hantzsch ester resulted in full conversion and good yields and stereoselectivity for products 5a and 5b .…”
Section: Resultsmentioning
confidence: 92%
“…Under these reaction conditions, the Cope product was observed directly. With regard to the functional group interconversion (Scheme B), we found that the alkylidene malononitrile moiety on 3a or 3c could be reduced efficiently with Hantzsch ester to a malononitrile moiety, which, in turn, could be converted to an ester under mild conditions . The dearomatized indole portion of the scaffolds could be rearomatized under Lewis acid-catalyzed or oxidative conditions, thus yielding 7a and 7b following K 2 CO 3 /MeOH-promoted N -triflate deprotection.…”
mentioning
confidence: 99%